Using biodegradable screws in treatment of hallux valgus - S. N. Leonova; I. V. Usoltsev (Acta Biomedica Scientifica)
The aim of the research was to assess using biodegradable screws in treatment of hallux valgus. We managed 40 female patients (average age 50 ± 2.51) with hallux valgus who where admitted to the orthopedic unit of Irkutsk Scientific Center of Surgery and Traumatology for operative treatment. All patients had X-ray, MRI and intraoperational examination of affected foot before the surgery and in postoperative period. All patients were operated using own surgical technique. Patients were divided into two groups: group 1 (22 patients) - osteosynthesis using biodegradable (PLGA) screws; group 2 (18 patients) - osteosynthesis using metal cannulated screws. In group 1 postoperative values of M1P1 angle were within normal range (9.67 ± 0.78°). According to MRI, proximal articular set angle (PASA) was corrected from 21.5 ± 0.35 to 4.17 ± 0.09°. 6 patients of the group 1 were complaining of pain and discomfort in the area of screw-head contacting soft tissues. The result of operative treatment in the group 2 resulted in the correction of M1P1 angle from 34 ± 1.63 to 7.67 ± 0.75°. After the surgery intraoperative PASA was back to the normal range (4.33 ± 0.34°). The comparison of the results of treatment of patients of groups 1 and 2 didn't reveal any statistically significant differences in the values of М1Р1, М1М2, М1М5 angles and PASA. The advantage of using biodegradable screws, compared to the metal ones, in the treatment of hallux valgus is the possibility of postoperative MRI of the foot with calculation of PASA to evaluate treatment results. The disadvantage of using biodegradable screws is engineering deficiency preventing screw-head from dipping into bone tissue and causing soft tissue traumatizing. Biodegradable and metal screws allow to obtain similar results of hallux valgus treatment.